Analisis Mutu Pelayanan Kesehatan Terhadap Kepuasan Pasien Di Rung Rawat Kelas III Rumah Sakit Duta Indah Jakarta - Cici Afriani; Asriwati Asriwati; Indra Ginting (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Patient satisfaction is an important indicator that must be considered in health services. Patient satisfaction is the result of the patient's assessment of health services by comparing what is expected in accordance with the reality of health services received in a hospital health setting. The aim of the study was to find out how patient satisfaction is in the Class III Inpatient Room at Duta Indah Hospital, Jakarta. The research design used in this study was an analytic survey with a cross sectional design. The population in this study includes all patients who are inpatient at Duta Indah Jakarta Hospital for the period September 2022 to January 2023 as many as 924 people. The number of samples to be examined according to slovin is 90 people. Data analysis was performed using univariate, bivariate and multivariate analysis. The statistical test used is the chi square test and logistic regression. The results of the chi square test showed that there was a relationship between reliability, responsiveness, empathy and assurance on health service satisfaction where the p-value = 0.000. From the results of multivariate analysis, it was found that the most influential variable in this study was the responsiveness variable with an OR value of 44,746. The conclusion is that there is an influence between reliability, responsiveness, direct evidence, empathy, assurance on health service satisfaction. It is recommended to the hospital. It is hoped that they can conduct training or workshops for health workers to improve the quality of services that must be improved, especially responsiveness, a fast response to dealing with patient complaints in the Class III Inpatient Room, Duta Indah Hospital, Jakarta.